The Impact of Super Apps Usage on Financial Literacy and Financial Behavior of Generation Z in Indonesia: A Literature Synthesis - Tabina Azzahra; Kurnia Fajar Afgani (Journal Integration of Management Studies, 2023)
Based on a literature review, this study explores the relationship between financial technology, financial literacy, and financial behavior. The findings suggest that financial technology is interconnected with financial literacy and behavior. Future research using quantitative or qualitative studies is recommended to investigate this relationship further. The proposed conceptual model can be utilized to examine the impact of super apps on Generation Z's financial literacy and financial behavior in Indonesia. This study contributes to the existing body of knowledge by shedding light on the potential implications of financial technology on individuals' financial knowledge and behaviours, particularly among the younger generation.